Towards a theoretical framework for human performance modelling within manufacturing systems design - Baines, Tim S.; Asch, R.; Hadfield, Linda; Mason, J. P.; Fletcher, Sarah R.; Kay, John M. (Elsevier, 2005)
The performance of direct workers has a significant impact on the competitiveness of many manufacturing systems. Unfortunately, system designers are ill equipped to assess this impact during the design process. An opportunity exists to assist designers by expanding the capabilities of popular simulation modelling tools, and using them as a vehicle to better consider human factors during the process of system design manufacture. To support this requirement, this paper reports on an extensive review of literature that develops a theoretical framework, which summarizes the principal factors and relationships that such a modelling tool should incorporate.